Amorphous WP‐Modified Hierarchical ZnIn2S4 Nanoflowers with Boosting Interfacial Charge Separation for Photocatalytic H2 Evolution. Issue 16 (4th May 2022) - Hao, Xuqiang; Shao, Yifan; Xiang, Dingzhou; Jin, Zhiliang
Abstract: The morphology design and loading of cocatalyst are effective strategies to enhance the light absorption capacity and separation efficiency of photogenerated carriers. This work successfully fabricates amorphous tungsten phosphide (WP)/hierarchical ZnIn2 S4 nanoflowers heterostructure (WP/ZnIn2 S4 ) with boosting interfacial charge separation for photocatalytic H2 evolution. The maximum H2 production rate of 6178 µmol g –1 is achieved over 10% WP/ZnIn2 S4 photocatalyst within 5 h, which is four times higher than that of pure ZnIn2 S4 . And a high photostability is also obtained. The enhanced photocatalytic hydrogen evolution activity can be attributed to the synergistic effect of amorphous WP and hierarchical ZnIn2 S4 nanoflowers. Amorphous WP as a cocatalyst can rapidly capture photogenerated electrons on the surface of ZnIn2 S4, improving the separation of photogenerated electron‐hole pairs. And the ZnIn2 S4 microflower with ultrathin nanosheets structure exposes more surface sites to anchor amorphous WP nanoparticles, which provides more active sites for hydrogen evolution. Additionally, amorphous WP greatly increases the light absorption range and prolongs the fluorescence lifetime of ZnIn2 S4 . This work provides a new idea for designing an effective cocatalyst‐modified semiconductor to improve photocatalytic activity. Abstract : An amorphous tungsten phosphide (WP) NPs/ZnIn2 S4 microflower photocatalyst is prepared by hydrothermal method and physical mixing method. The highest H2 production rate of 1235.6 μmol h −1 g −1 can be achieved over 10% WP/ZnIn2 S4, which is about four times higher than pure ZnIn2 S4 . The enhanced photocatalytic activity can be attributed to the synergistic effect of amorphous WP and hierarchical ZnIn2 S4 nanoflowers.